Portuguese Version of the Short-Form Survivor Unmet Needs Survey: Psychometric properties in a sample of Azorean cancer survivors - Sousa, Marina (2021)
This study aims to investigate the psychometric properties and the factor structure of the Portuguese version of the Short-Form Survivor Unmet Needs Survey (SF-Suns). The sample comprises 151 cancer survivors from the Azores (Portugal), who completed a survey assessing unmet needs (SF-Suns), psychological symptoms (HADS) and quality of life (QLQ-C30). A Confirmatory Factorial Analysis (CFA) and an Exploratory Factorial Analysis (EFA) were conducted to assess the factorial structure of the SF-Suns. The results of the CFA indicated that the original SF-Suns model did not present an adequate fit to the data. Therefore, an EFA was conducted to explore the factor structure of the scale in the current sample. The resulting four-factor structure differed from the structure of the original version of the scale. The measure presented adequate internal consistency (good Cronbach’s alpha values for each factor and for the total scale) and showed convergent validity (moderate correlations with anxiety, depression and some quality of life dimensions). The Portuguese version of the SF-Suns is a reliable and psychometrically valid measure for evaluating Azorean cancer survivors’ unmet needs. The dissemination of its use can allow tailoring specific clinical and psychotherapeutic responses to their needs.